If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying C + 4c = -90 Solving C + 4c = -90 Solving for variable 'C'. Move all terms containing C to the left, all other terms to the right. Add '-4c' to each side of the equation. C + 4c + -4c = -90 + -4c Combine like terms: 4c + -4c = 0 C + 0 = -90 + -4c C = -90 + -4c Simplifying C = -90 + -4c
| mx^2-2x-m-1=0 | | 6x-10=-34 | | 7ab+ab-9ab= | | 0.66a=6 | | 3x+0+8=0 | | 3x^3-13x^2+12x-6=0 | | 9x-7y=y | | 10x-y=12 | | X+.75y=15 | | -(8-b)+12b-9=-6b+2b | | 1=x-6 | | 3(2x-1)+2=5x-1 | | x+4y+2z=0 | | 2x-3y+2=2 | | 6+4a=-8 | | 0.66r=8 | | 72=-3(x+4)-21x | | K-7=10 | | 3+z=18 | | 1.5r=8 | | -5x=18-3x | | 0.8m=80 | | -6+4y=-12 | | 5x-4(x-6)=1 | | h=-16t^2+150t+1 | | 2x+y=10-3x | | 2x^2-15x+15=8-x^2-5x | | (u+3)2=2u+11u+15 | | X^4-7x+3=0 | | 2x^4-7x+3=0 | | 2x+3x-15=25 | | -2+x-4x=11 |